The Effectiveness of the Eco-Athletics Model on Improving Fundamental Motor Skills and Environmental Awareness of Physical Education Students at Pamulang University: The Effectiveness of the Eco-Athletics Model on Improving Fundamental Motor Skills and Environmental Awareness of Physical Education Students at Pamulang University - Veni Elisyah; Rohmat Nurhidayat; Ilona Pratiwi Hutabarat (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effectiveness of the Eco-Athletics learning model in improving fundamental motor skills and environmental awareness among students of the Physical Education Study Program at Pamulang University. The research employed a quasi-experimental method using a pre-test and post-test design with a control group. It was conducted at the open sports field and educational park of Pamulang University for 8 weeks. Participants consisted of 60 students selected through simple random sampling and divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received treatment using the Eco-Athletics model, which integrates outdoor physical activities and ecological education, while the control group followed conventional physical education. Instruments used included the Test of Gross Motor Development (TGMD-2) to measure motor skills and a validated environmental awareness questionnaire. Data analysis was performed using SPSS 25 with normality tests, paired t-tests, independent ttests, and Cohen's d effect size. Results indicated significant improvements in fundamental motor skills and environmental awareness in the experimental group compared to the control group (p < 0.05). The effect sizes for both variables were large (Cohen's d > 1.5). These findings suggest that the Eco-Athletics model is an effective pe